2018
DOI: 10.1108/he-10-2017-0055
|View full text |Cite
|
Sign up to set email alerts
|

Gamification of health education

Abstract: Purpose-The use of modern technology has many challenges and risks. However, by collaborating with schoolchildren, ideas to effectively promote health and learning in school can be identified. The purpose of this paper is to examine how a participatory approach can deepen the understanding of how schoolchildren relate to and use gamification as a tool to promote physical activity and learning. Design/methodology/approach-Inspired by the concept and process of empowerment and child participation, the methodolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 58 publications
0
11
0
2
Order By: Relevance
“…The findings of the current study showed a significant increase in the knowledge of the students regarding leptospirosis following health education by gamification ( p < 0.01). The success of using gamification as a tool to promote health education by involving the participants in various physical activities was also demonstrated in earlier studies [45,58]. Gamification is a promising activity that helps people maintain and recall knowledge in interactive ways due to increased attention, commitment, and motivation.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…The findings of the current study showed a significant increase in the knowledge of the students regarding leptospirosis following health education by gamification ( p < 0.01). The success of using gamification as a tool to promote health education by involving the participants in various physical activities was also demonstrated in earlier studies [45,58]. Gamification is a promising activity that helps people maintain and recall knowledge in interactive ways due to increased attention, commitment, and motivation.…”
Section: Discussionmentioning
confidence: 77%
“…Most of the respondents obtained good scores for the knowledge on disease treatment and prevention. This is not surprising, as most people believe that maintaining personal hygiene can prevent all types of infections [52,56,57,58].…”
Section: Discussionmentioning
confidence: 99%
“…En este sentido, un meta análisis sobre la efectividad de la gamificación ha identificado resultados positivos del método de gamificación para niños de 6 a 10 años en diversas disciplinas y otros aspectos del desarrollo, mostrando que la efectividad del diseño posterior a la prueba muestra que el método de gamificación puede mejorar las habilidades cognitivas, actitud, lenguaje, salud y habilidades socioemocionales (Fadhli, Brick, Setyosari, Ulfa, y Kuswandi, 2020). Aspecto en sintonía con un estudio en escolares de 10 a 12 años que proporciona conceptos de gamificación y combinaciones de diferentes aplicaciones tecnológicas para aumentar la salud y el aprendizaje, así como los aspectos motivacionales sugeridos por los escolares (Kostenius, Hallberg y Lindqvist, 2018). En esta línea, encontramos experiencias exitosas en escolares de primaria (Jiménez, Navas-Parejo, Villalba, et al, 2019) de matemáticas (Claudio, Machancoses, y Piqueras, 2019) en educación secundaria obligatoria (Monguillot-Hernando, González-Arévalo, Zurita-Mon, et al, 2015) y adultos (Aguilar, 2019;Prieto-Andreu, 2020;Kinio, Dufresne, Brandys, y Jetty, 2019).…”
Section: Discussionunclassified
“…En concreto, el estudio de la gamificación en el área de la salud es reciente (Kostenius, Hallberg y Lindqvist, 2018), así como en la promoción de hábitos de vida saludables (Ferreira, 2019;Hortigüela-Alcalá, Hernando-Garijo, y Pérez-Pueyo, 2018) en términos del conocimiento de actividad física (Monguillot Hernando, González Arévalo, Zurita Mon, Almirall Batet, y Guitert Catasús, 2015), una nutrición saludable y su adherencia a la dieta mediterránea (Gómez del Río, González-González, Martín-González, Navarro-Adelantado, Toledo-Delgado, y García-Peñalvo, 2019).…”
Section: Introducción A) Fundamentación Teóricaunclassified
“…Actually, Werbach and Hunter (2012), showed how gamification can generate in the students a significant segregation of dopamine, which intensifies neurological activity, increases the motivation, cognition, attention and the sense of the learning process. Gamification seems to be an effective tool for the promotion of physical activity, sports and other healthy lifestyle habits in the school environment (Kostenius, Hallberg, & Lindqvist, 2018;Martín-Moya, Ruiz-Montero, Chiva-Bartoll, & Capella-Peris, 2018;Monguillot, González-Arévalo, Zurita, Almirall, & Guitert, 2015), university (Pérez-López, Rivera-García, & Delgado-Fernández, 2017), and non-school spaces (Johnson, Deterding, Kuhn, Staneva, Stoyanove, & Hides, 2016). Instead, the practice and teaching of activities related to fitness and health should be done through fun and motivational activities.…”
Section: Introductionmentioning
confidence: 99%